KONTRIBUSI EKONOMI SYARIAH DALAM MENDUKUNG PERTUMBUHAN GREEN ECONOMY BERKELANJUTAN - Jureid (Program Studi Ekonomi Syariah Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2024)
Sharia Economy and Green Economy: A Synergy for Sustainable Development. Sharia economy and green economy hold significant potential in supporting sustainable economic growth. This study aims to explore the contribution of the sharia economy to developing an inclusive and environmentally friendly green economy. Utilizing a qualitative approach with a literature review method, the research examines various sources such as books, academic journals, research reports, and related documents to identify the relevance of theories and practices. The findings indicate that the principles of the sharia economy, such as justice, maslahah (public benefit), and i’tidal (balance), align with the goals of the green economy, which emphasize resource efficiency, low carbon emissions, and social inclusivity. The sharia economy promotes ethical and sustainability-oriented practices, employing instruments like zakat (almsgiving), waqf (endowment), and profit-sharing schemes to fund environmental projects and address social inequalities. However, implementing the Sharia economy faces challenges, such as a lack of regulations and public awareness. This study concludes that cross-sector collaboration and policy support are crucial to strengthening the role of the Sharia economy in achieving a sustainable green economy. These findings are expected to contribute academically and serve as practical guidelines for policymakers in promoting an economic transformation that is fairer, more environmentally friendly, and sustainable.